Identification of a Potential MiRNA–mRNA Regulatory Network for Osteoporosis by Using Bioinformatics Methods: A Retrospective Study Based on the Gene Expression Omnibus Database - Lin, Shi; Wu, Jianjun; Chen, Baixing; Li, Shaoshuo; Huang, Hongxing (Frontiers in Endocrinology, 2022)
Abstract: As a systemic skeletal dysfunction, osteoporosis (OP) is characterized by low bone mass, impairment of bone microstructure, and a high global morbidity rate. There is increasing evidence that microRNAs (miRNAs) are associated with the pathogenesis of OP. Weighted gene co-expression network analysis (WGCNA) is a systematic method for identifying clinically relevant genes involved in diseases pathogenesis. However, the study of the miRNA-mRNA regulatory network in combination with WGCNA in OP is still lacking. Methods: The GSE93883 and GSE7158 microarray datasets were downloaded from the GEO database. Differentially expressed miRNAs (DE-miRNAs) and differentially expressed genes (DEGs) were analyzed with the limma package. OP-related miRNAs from the most clinically relevant module were identified by WGCNA method. The overlap of DE-miRNAs and OP-related miRNAs were identified as OP-related DE-miRNAs. Both upstream transcription factors and downstream targets of OP-related DE-miRNAs were predicted by FunRich. An intersection of predicted target genes and DEGs were confirmed as downstream target genes of OP-related DE-miRNAs. Using clusterProfiler in R, GO annotation and KEGG pathway enrichment were performed on target genes. Finally, both the PPI network and miRNA-mRNA network were constructed and analyzed. Results: 79 OP-related DE-miRNAs were obtained, most of which were predicted to be regulated by SP1. Subsequently, 197 downstream target genes were screened out. The target genes were enriched in multiple pathways, including signaling pathways closely related to the onset of osteoporosis, such as Ras, PI3K-Akt, and ErbB signaling pathways. Through the construction of the OP-related miRNA-mRNA regulatory network, a hub network that may play a prominent role in the formation of OP was documented. Conclusion: By using weighted gene co-expression network analysis, we constructed a potential OP-related miRNA-mRNA regulatory network, offering a novel perspective on miRNA regulatory mechanisms in OP. Keywords: osteoporosis, miRNAs, WGCNA, bioinformatics analysis, miRNA-mRNA regulatory network